Pengaruh Bermain Peran Makro Terhadap Kemampuan Sosial Anak Usia 5-6 Tahun - Erni Ani; Azizah Amal; Angri Lismayani (Jurnal Kajian Anak)
The purpose of this study is to determine the influence of macro-level games on the social skills of children aged 5–6 years at Sitti Khadija Tingkara Kindergarten, North Luwu. The analysis method used in this study is quantitative and based on the category of pseudo-experimental analysis. The sample used in this study consisted of 20 children, namely 10 children in the experimental group and 10 children in the control group. The data collection techniques used in this study are observation, test, and documentation. The data analysis method in this study consists of descriptive statistical analysis and nonparametric analysis using the Wilcoxon Sign Rank Test. Based on the results of the Wilcoxon Sign Rank Test, the Sig value (2-tailed) was determined. If 0.005 is less than 0.05, H0 is discarded and H1 is retained. Based on this, there is a difference in the social maturity score of children aged 5 to 6 years